The Influence of Leverage, Committee, and Financial Distress on Tax Avoidance (Empirical Study of Consumer Companies were Listed on the Indonesia Stock Exchange (IDX) from 2018 Until 2022) - Tiur Ayumi Briggita Bakkara; Ardan Gani Asalam (Jurnal Multidisiplin Madani, 2023)
Tax Avoidance is a legal action taken by taxpayers to minimize the compliance costs that they incur when fulfilling their tax obligations. This action is very detrimental to the state because taxes are one of the largest sources of state revenue. The goal of the research is to establish the effect of leverage, audit committees, and financial distress on tax avoidance, in conjunction with the proxy CETR. The population in this research is comprised of consumer companies were listed on the Indonesia Stock Exchange (IDX) from 2018 until 2022. Using purposive sampling approaches, samples were acquired from 14 companies over a five-year period, producing an overall total of 70 samples. In this research, the analysis of panel data regression was conducted using the Eviews 12 tool. According to the outcomes of this research, leverage, audit committees, and financial distress are all having an impact on tax avoidance. Leverage and the audit committee have no impact on tax avoidance, whereas Financial Distress has a positive impact